Severe storms and their efects in sub-Mediterranean Slovenia from the 14th to the mid-19th century - Ogrin, Darko (Acta geographica Slovenica, 2007)
The paper presents an overview of severe storms and a reconstruction of periods with their reiterative occurrence in sub-Mediterranean Slovenia in the warm half of the year during the so-called pre-instrumental period. The data were gathered in secondary and tertiary historical sources, chronicles first and foremost. The presented chronology does not provide a complete reconstruction because of insufficient data, yet it offers a basic insight into the periods of frequenter occurrence of these phenomena. Outstanding are the 17th and the 18th centuries, especially their first halves whose weather conditions rank among the most unfavourable in the last millennium. In addition to severe winters with damages done by frosts, dry or too wet summers, 12 violent storms in the 17th century and 16 in the 18th century caused great damage and considerably aggravated the conditions of living. The occurrence of storms in the first halves of the 17th and the 18th centuries was equal to that at the end of the 20th century, when frequenter occurrence of such weather extremes is mainly believed to be caused by the general warming of the atmosphere. It is evident from the chronicle that the characteristics of severe storms and the kinds of resulting damage have not significantly changed until today. The only phenomenon that has not been recorded in the recent history of climate is such a sharp drop in temperature in the lower parts of the Primorska (Littoral) region during an August storm as to cause that snow fell, which, supposedly, happened in August 1710.
Keywords: paleoklimatologija; klimatske spremembe; vremenske ujme; nevihte; neurja; jugozahodna Slovenija